Correlation between the Modified Systemic Lupus Erythematosus Disease Activity Index 2000 and the European Consensus Lupus Activity Measurement in juvenile systemic lupus erythematosus - Sato, J. O. [UNESP]; Corrente, J. E. [UNESP]; Saad-Magalhães, C. [UNESP] (SAGE Publications, 2016)
Objective The objective of this study was to assess Modified Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K) and European Consensus Lupus Activity Measurement (ECLAM) disease activity correlation in addition to their respective correlation to Pediatric Systemic Lupus International Collaborative Clinics/American College of Rheumatology (SLICC/ACR) Damage Index (Ped-SDI), in juvenile systemic lupus erythematosus (JSLE). Methods The activity indices were scored retrospectively and summarized by adjusted means during follow-up. The Ped-SDI was scored during the last visit for those with more than six months follow-up. Pearson correlation between the Modified SLEDAI-2K and ECLAM, as well as Spearman correlations between the Modified SLEDAI-2K, ECLAM, and Ped-SDI were calculated. The receiver operating characteristic (ROC) curve was calculated for both activity indices discriminating damage measured by Ped-SDI. Results Thirty-seven patients with mean age at diagnosis 11 ± 2.9 years and mean follow-up time 3.2 ± 2.4 years were studied. The Modified SLEDAI-2K and ECLAM adjusted means were highly correlated (r = 0.78, p < 0.001). Similarly, Spearman correlation between the activity indices was also high (rs > 0.7, p < 0.001), but Modified SLEDAI-2K and ECLAM correlation with Ped-SDI was only moderate. ROC analysis discriminant performance for both activity indices resulted in area under curve (AUC) of 0.74 and 0.73 for Modified SLEDAI-2K and ECLAM, respectively. Conclusion The high correlation found between the Modified SLEDAI-2K and ECLAM adjusted means indicated that both tools can be equally useful for longitudinal estimates of JSLE activity.
Keywords: Activity; childhood-onset systemic lupus erythematosus; damage; ECLAM; juvenile systemic lupus erythematosus; Modified SLEDAI-2K